Being local worldwide: ABB and the challenge of global management (Ithaca, 2001)
"Fortune called Asea Brown Boveri, the giant multinational corporation created in 1987, "the most successful cross-border merger since Royal Dutch linked up with Britain's Shell in 1907." The coming together of two longtime national champions in the electrotechnical industry, Sweden's ASEA and Switzerland's Brown Boveri, marked the birth of a company with truly global aspirations, one whose apparent genius for combining strong central planning with local autonomy for its plants has made it a trendsetter.An international team of researchers assesses the dynamic interplay of the forces of convergence and diversity present in ABB. Together they examine the actual workings of this multinational-in order to learn to what degree the corporate strategies are achieved in its plants. Based on a multilevel organizational study, their book compares seven plants in six countries on three continents."